Karakteristik Nanopowder Manganese Oxide (MnO) Hasil Sintesis Sol-Gel - Sasongko, Muhammad Ilman Nur (Universitas Merdeka Malang, 2022)
Phase and morphology characterization of powder Manganese Oxide (MnO) aims to reduce the grain size of micro sized MnO material into nano size using sol-gel method with sintering time variations. The results showed the phase changes in the MnO 30 minutes, 60 minutes and 90 minutes indicates the size of the crystal grains of 47,3.nm, 68.299 nm, and 84, 547 nm. (2) The change is significant, because the crystals MnO Raw at 143.44 nm. (3) Changes in the morphology shows a triangular Raw MnO after synthesis, transformed into spherical grains by agglomeration membranes MnO. The study has managed to change the grain size of micro sized MnO into nano.